Production, Transport, and Destruction of Dust in the Kuiper Belt: The Effects of Refractory and Volatile Grain Compositions - Thomas Corbett; Alex Doner; Mihály Horányi; Pontus Brandt; Will Grundy; Carey M. Lisse; Joel Parker; Lowell Peltier; Andrew R. Poppe; Kelsi N. Singer; S. Alan Stern; Anne J. Verbiscer (The Astrophysical Journal Letters)
The Venetia Burney Student Dust Counter (SDC) on board the New Horizons spacecraft measures the spatial and size distributions of dust along its trajectory. Models based on early SDC measurements predicted a peak dust number density at a heliocentric distance of ∼40 au, followed by a rapid decline. Instead, SDC observed dust fluxes 2–3 times higher than predicted between 40 and 60 au. One potential explanation for this discrepancy is that SDC may be encountering icy grains with different dynamical behavior than previously modeled silicate grains. Due to ultraviolet photosputtering, water–ice grains rapidly erode and migrate outward, significantly contributing to the measured dust number densities only at distances ≳40 au. We present a model of silicate and ice grain dynamics in the outer solar system, considering gravitational and radiation forces and grain erosion. Using SDC data, we estimate that the mass production rate of ice grains between 0.1 and 10 μ m in the Kuiper Belt (KB) would need to be 20–70 times higher than that of silicate grains. However, KB grains are expected to be refractory/volatile mixtures rather than pure silicate or ice. Thus, we briefly explore simple models of more realistic mixed-grain cases to further gauge the effects of grain composition on the equilibrium dust distribution. Future SDC measurements at greater distances will test the model predictions and further constrain silicate and ice grain production rates in the KB.